Effect of the GASING Method on Addition Speed in Students with Visual Impairments: A Single-Subject A-B-A Study - Atsir Al Atsari; Dody Bakhtiar Al Anshori; Sistriadini Alamsyah Sidik; Dedi Mulia (Department of Special Education, 2025)
Children with visual impairments often face challenges in mastering basic mathematics. This study aimed to examine the effect of the GASING Method in improving addition calculation speed among these students. Adopting a quantitative approach, a Single Subject Research (SSR) design with an A-B-A design was used. This study involved one subject, a 6th-grade elementary school student. The instrument was a worksheet consisting of 30 addition problems, presented in Braille format. Data were analyzed visually, including trends, levels, stability, and overlap percentages between phases. The research results indicated a significant effect of the GASING Method intervention. This was particularly evident from the very low percentage of data overlap: 17 percent between Phase A1 (Baseline) and Phase B (Intervention), and 0 percent between Phase B and Phase A2 (Withdrawal). The intervention successfully reduced the subject’s average calculation time from 3.0 seconds in the A1 phase to 2.2 seconds in the B phase, further improving to 1.6 seconds in the A2 phase. This represents a significant overall reduction in completion time. Thus, it is concluded that the GASING Method is effective in improving the addition calculation speed of children with visual impairments